Performance of a UASB reactor for the treatment of anionic surfactant wastewater - Pizzo, Matheus Marques; Braga, Juliana Kawanishi; Rodriguez, Renata Piacentini; Pires, Lorena Oliveira [UNESP]; Sancinetti, Giselle Patrícia (Inderscience Publishers, 2023)
This study evaluated the biological removal of organic matter (chemical oxygen demand, COD) and surfactant from laundry wastewater (LW) employing an Upflow Anaerobic Sludge Blanket reactor at 30°C. The hydraulic retention time and operation time were 48 h and 317 days, respectively. The treatment was divided into seven phases, changing the concentrations of the COD and surfactant influents (600-1,000 mg COD/L and 2-10 mg/L). Removal efficiencies were 85.83-95.46% and 35-64% for the COD and surfactant, respectively. The use of real LW promoted lower surfactant removal compared to the phases that employed industrial detergent, except for the first phase with LW, probably due to the process of adsorption into the biomass. The degradation kinetics indicated a higher COD and surfactant consumption by biomass in the first 10 h of hydraulic detention.
Keywords: anaerobic digestion; HRT; laundry wastewater